Crome, Andrew and James McGrath (eds.), Time and Relative Dimensions in Faith: Religion and Doctor Who. (2nd May 2019) - Balstrup, Sarah
Abstract : Crome, Andrew and James McGrath (eds.), Time and Relative Dimensions in Faith: Religion and Doctor Who. London: Darton, Longman & Todd, 2013, pp. 367, ISBN: 9-780-23253-021-6.